A recurrent hydatid cyst of the thigh diagnosed 13 years after initial presentation. (2018) - Barkati, Sapha; Butler-Laporte, Guillaume; Ndao, Momar; Kabiawu Ajise, Oluyomi; Semret, Makeda; Yansouni, Cédric P.; Libman, Michael
Abstract: This case presents a hydatid cyst of the thigh in a 57-year-old patient born and raised in rural Montenegro. He presented with a painful erythematous mass on the lateral aspect of the right thigh at the site of a previous cystic mass resection 13 years earlier. Complete surgical resection was conducted, histopathology revealed laminated membranes and polymerase chain reaction was positive for Echinococcus granulosus. Primary musculoskeletal hydatidosis is a rare entity and diagnosis is challenging. Any cystic lesion in a patient from an endemic area should raise the possibility of echinococcosis, regardless of anatomic location. The key aspects of diagnosis, albendazole treatment and surgical management are discussed.